2018
DOI: 10.3390/nu10121986
|View full text |Cite
|
Sign up to set email alerts
|

Serum Nutrient Levels and Aging Effects on Periodontitis

Abstract: Periodontal disease damages tissues as a result of dysregulated host responses against the chronic bacterial biofilm insult and approximately 50% of US adults >30 years old exhibit periodontitis. The association of five blood nutrients and periodontitis were evaluated due to our previous findings regarding a potential protective effect for these nutrients in periodontal disease derived from the US population sampled as part of the National Health and Nutrition Examination Survey (1999–2004). Data from over 15,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 115 publications
(167 reference statements)
5
37
0
1
Order By: Relevance
“…The 2011–2014 US National Health and Nutrition Examination Survey data linked FA inadequacy to periodontal disease severity and suggested its use to reduce disease severity (Luo et al, 2018). Ebersole, Lambert, Bush, Huja, and Basu (2018) also recommended FA intake to prevent the increasing prevalence of periodontal diseases occurring with ageing.…”
Section: Introductionmentioning
confidence: 99%
“…The 2011–2014 US National Health and Nutrition Examination Survey data linked FA inadequacy to periodontal disease severity and suggested its use to reduce disease severity (Luo et al, 2018). Ebersole, Lambert, Bush, Huja, and Basu (2018) also recommended FA intake to prevent the increasing prevalence of periodontal diseases occurring with ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Amengual et al, also reported that β-carotene reduced the adiposity of body, downsize of adipocytes and blood leptin levels using in vivo experiment [46]. Importantly, Ebersole et al, have shown that lower β-carotene levels in blood were found in moderate/severe periodontitis patients [40].…”
Section: β-Carotenementioning
confidence: 97%
“…There is in fact a significant association between age and the severity of periodontal disease. The deterioration of the immune system and the insufficiency of certain blood nutrients, such as cis-β-carotene folate and vitamin D, which are frequently observed in elderly, might be involved in the relationship between aging and periodontal disease 15,16 .…”
Section: Jrpmsmentioning
confidence: 99%
“…Smoking has been firmly associated independently with osteoporosis by a plethora of studies 16,17 . Baccaro LF.…”
Section: ) Smokingmentioning
confidence: 99%
See 1 more Smart Citation